CHOROIDAL NEOVASCULARIZATION IN A CASE OF CHORIORETINAL COLOBOMA TREATED WITH INTRAVITREAL ANTI-VEGF INJECTONS: A CASE REPORT - Dicky Budiman Simanjuntak; Andi Arus Victor; Gitalisa Andayani (Indonesian Vitreoretinal Society, 2022)
Introduction: Chorioretinal coloboma (CRC) results from abnormal closure of the embryonic fissure. Choroidal neovascularization (CNV) is a rare complication that associated with coloboma of the choroid. VEGF is an important factor in the development of CNV. Case Report: A 52-year-old woman with gradual blurred vision of the left eye since 4 months ago. Right eye was already blurred since she was a child with uncorrected visual acuity (UCVA) was 0.5/60. Her right iris showed coloboma in inferior and chorioretinal coloboma. UCVA of the left eye was 6/20. Her left iris showed inferior coloboma, chorioretinal coloboma and macular edema with soft drusen. Macular optical coherence tomography (OCT) confirmed macular subretinal fluid, and indicated a CNV lesion of the left eye. She underwent a loading dose of three monthly intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections (bevacizumab) for the left eye. One month after completion of treatment, UCVA of the left eye improved to 6/12. Discussion: CNV is a complication associated with CRC. Intravitreal Anti-VEGF treatment using loading dose regimen is shown to be effective in treating CNV. One month after completion of treatment, UCVA of the left eye improved. Conclusion: Chorioretinal coloboma is a rare posterior segment congenital anomaly. Classical, bilateral coloboma of the choroid and iris indicates a deformation of the choroidal fissure closure. Coloboma of the choroid can have a complication such as choroidal neovascularization. Treatment with a loading dose of three monthly intravitreal anti-VEGF injections showed good anatomical and functional results.